PRECISION MECHANICS IN AUDIO-VISUAL DEVICES: ENHANCING QUALITY IN MEDIA PRODUCTION - Kale, Shantanu; R. Deore, Narendra (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Precision engineering has emerged as a cornerstone in the development of next-generation audio-visual (AV) devices, where stringent demands on vibration control, alignment, and signal fidelity dictate system performance. This study systematically explores the fundamentals of precision mechanics relevant to AV systems, focusing on kinematic couplings, bearings, actuators, and tolerance stack-up analysis. Design methodologies, including finite element analysis (FEA), modal analysis, multibody dynamics, and control-co-design, are presented as critical tools for predicting system behavior and enabling robust mechatronic integration. Comparative modeling approaches are discussed with emphasis on yield, reproducibility, and optimization-driven material selection. Furthermore, precision manufacturing and surface engineering methods such as ultra-precision machining, additive manufacturing, and nano-coatings are examined alongside the role of cleanroom assembly and integrated metrology. By linking mechanical precision with advanced simulation and manufacturing strategies, this work highlights the path toward achieving reproducibility, stability, and high performance in AV products ranging from microphones and projectors to gimbals and speakers. The synthesis of design, materials, and process control underscores the multidisciplinary nature of AV system innovation.